Reversible Response of Luminescent Terbium(III)–Nanocellulose Hydrogels to Anions for Latent Fingerprint Detection and Encryption. Issue 23 (8th May 2018) - Hai, Jun; Li, Tianrong; Su, Junxia; Liu, Weisheng; Ju, Yanmin; Wang, Baodui; Hou, Yanglong
Abstract: Fingerprint fluorescence imaging has become one of the most prominent technologies in the field of forensic medicine, but it seldom considers the security protection of detection information, which is of great importance in modern society. Herein we demonstrate that luminescent Tb III –carboxymethyl cellulose (CMC) complex binding aptamer hydrogels that are reversibly responsive to ClO − /SCN − can be used for the selective detection, protection, and storage of fingerprint information. The imaging information of the fingerprint can be quenched and recovered by ClO − /SCN − regulation, respectively, resulting in reversible on/off conversion of the luminescence signals for the encryption and decryption of multiple levels of information. The present study opens new avenues for multilevel imaging, data recording, and security protection of fingerprint information with tunable fluorescent hydrogels. Abstract : Safe and secure : A hydrogel based on a luminescent Tb III –carboxymethyl cellulose complex was developed for the selective detection, protection, and storage of fingerprint information. The imaging information could be quenched with ClO − ions and recovered by the addition of SCN −, thus leading to reversible on/off switching of the luminescence signal for fingerprint information encryption and decryption.